The ISO 9004: 2018 standard and the application of the balanced scorecard for sustained success (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2020)
The importance of quality as a competitive variable has motivated ISO standards to increasingly focus on the strategic approach. In this tendency, the ISO 9004 Standard, which was initially complementary to the ISO 9001 Standard and focused on improving performance, became, from the 2018 version, a guide to achieve sustained success, based on the strategy and sustained by the application of quality principles to the whole organizational field. However, this standard offers a mass of numerous and fragmented guidelines, without indicating the way in which they are articulated to achieve the proposed result, which is why it is required to use tools that make visible the connection scheme between the guidelines of the ISO 9004: 2018 standard to achieve sustained success, which would favor the applicability of said standard. In this sense, this documentary and analytical work, based on the literature review, proposes to use the Balanced Scorecard (BSC) model to untangle the chain of causality that interlinks the orientations contained in it. To this purpose, these guidelines are translated into the expression of objectives and tied by means of a strategic map. The work concludes that the BSC is effective in articulating the guidelines of the ISO 9004:2018 Standard in a causality scheme that allows simplifying its application, making its results visible and relating it to the organizational strategic management system.
Keywords: ISO 9004: 2018 standard; strategic management; quality management; balanced scorecard